Hard magnetic SmCo5-Cu nanocomposites produced by severe plastic deformation. (1st March 2023) - Staab, Franziska; Bruder, Enrico; Schäfer, Lukas; Skokov, Konstantin; Koch, David; Zingsem, Benjamin; Adabifiroozjaei, Esmaeil; Molina-Luna, Leopoldo; Gutfleisch, Oliver; Durst, Karsten
Abstract: Textured nanocrystalline SmCo5 -Cu magnets are produced by high-pressure torsion (HPT) of powder blends consisting of SmCo5 and Cu powder. The process enables a free selection of the magnetic phase and the grain boundary phase and overcomes limitations imposed by the phase diagram as in conventional sintering routes. Different numbers of rotations and thus strains, and the effect of the amount of Cu as the binder phase are investigated systematically with regard to the microstructure, and magnetic properties after HPT. With increasing number of rotations, a structural refinement, and an increasing coercivity are observed. TEM and EBSD analyses reveal fragmentation via particle fracture and plastic deformation as microstructural refinement processes. TEM analyses showed an amorphous structure of strongly deformed SmCo5 particles after 20 rotations during the HPT process. The magnetic hardening is ascribed to the microstructural refinement and the magnetic decoupling of the hard magnetic SmCo5 grains by Cu. XRD and microstructural analyses as well as magnetic hysteresis measurements indicate the formation of a texture during the HPT process. Consequently, the work demonstrates a new approach for the generation of textured nanostructured hard magnets. Graphical abstract: Image, graphical abstract